Board Characteristics and Managerial Overconfidence in an Emerging Market - Khajavi, Shokrollah; Dehghani, Golamreza (International Journal of Economics and Financial Issues, 2016)
This research investigates the relationship between board characteristics and managerial overconfidence of 107 listed companies in Tehran Stock Exchange during 2006-2012. In addition, financial data of the year 2005 have been used to calculate research variables. Furthermore, in order to examine the hypotheses, the research uses pooled/panel regression and ML-Binary Logit Model. Capital expenditure and overinvestment on assets criteria have been used to measure managerial overconfidence, and board size, board independence and CEO duality have been considered as board characteristics. The findings indicate that only board independence has negative and significant effect on managerial overconfidence. Besides, firm age as control variable has a direct and significant effect on capital expenditure. Keywords: board size, board independence, CEO duality, managerial overconfidence, capital expenditure, and overinvestment on assets JEL Classifications: D03, G32